2011
DOI: 10.1111/j.1525-1446.2011.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Hand Hygiene Education in a Basic Nursing School Curricula

Abstract: The lack of compliance with HH standards among students lead to poor compliance among health care professionals in praxis. Consequently, the role of educational institutions in the prevention of hospital-acquired infections is significant, if the effectiveness of HH education is to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 27 publications
3
48
0
10
Order By: Relevance
“…This situation intensifies the need for a comprehensive curriculum to be introduced early in the training of health sciences students to incorporate prevention and control of infectious diseases. Hand hygiene is an important healthcare issue globally and is the single most cost-effective and practical measure to reduce the incidence of healthcare-associated infection and the spread of antimicrobial resistance across all settings from advanced health care systems to primary healthcare centers as well as to health workers 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…This situation intensifies the need for a comprehensive curriculum to be introduced early in the training of health sciences students to incorporate prevention and control of infectious diseases. Hand hygiene is an important healthcare issue globally and is the single most cost-effective and practical measure to reduce the incidence of healthcare-associated infection and the spread of antimicrobial resistance across all settings from advanced health care systems to primary healthcare centers as well as to health workers 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nursing school curriculum in educational institutions in Kosovo must be enriched and updated with WHO materials about HH. An effective educational program, in the context of formal training and the nursing school curriculum, is very important due to the fact that the poor knowledge and low HH practical skills among students may have a significant negative impact in the HH compliance later in their daily clinical work (Kelcíkova et al, 2012). Similar to this study, Huang et al, (2012) assessed the impact of an educational program and found a significant increase of knowledge (p <0.001) but for a longer period of time (4 months) and with two groups (experimental and control).…”
Section: Discussionmentioning
confidence: 99%
“…One of the WHO multimodal strategies to increase awareness and knowledge about HH is the training about HH understanding and practices (WHO, 2009). Numerous authors have conducted studies to assess the HH knowledge of undergraduate students and their level of knowledge was rather low (Nair et al, 2014;Van de Mortel et al, 2010;Herbert et al, 2013;Feather et al, 2000;Thakker&Jadhav, 2015;Garcia-Zapata et al, 2009;Kelcíkova et al, 2012). Therefore, the inclusion of HH in the undergraduate curriculum is considered an emergency issue (Chatterjee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, una adecuada formación tanto en las etapas pregrado 19 , como en la etapa profesional 20 , a través de intervenciones formativas específicas, se presenta igualmente como un medio de intervención eficaz. De hecho, muchos de estos estudios han evidenciado el impacto positivo de la formación en higiene de las manos, tanto en los conocimientos y las percepciones de los profesionales sanitarios 14,17,21 , como en su adecuación a los estándares y prácticas seguras 17,22,23 .…”
Section: En España Según El úLtimo Informe Estudio De Prevalencia unclassified